Effects of bone morphogenetic proteins on epithelial repair. Issue 21 (November 2021) - Hou, Yu; He, Yu-Xi; Zhang, Jia-Hao; Wang, Shu-Rong; Zhang, Yan
Epithelial tissue has important functions such as protection, secretion, and sensation. Epithelial damage is involved in various pathological processes. Bone morphogenetic proteins (BMPs) are a class of growth factors with multiple functions. They play important roles in epithelial cells, including in differentiation, proliferation, and migration during the repair of the epithelium. This article reviews the functions and mechanisms of the most profoundly studied BMPs in the process of epithelial damage repair and their clinical significance.